Eutrophication: Causes, Consequences and Control 2010
DOI: 10.1007/978-90-481-9625-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Plant Nutrient Phytoremediation Using Duckweed

Abstract: Over the last 40 years a great deal of research has been published on the use of duckweed to treat wastewater both from point sources (feedlots, food processing plants) and from non-point sources. These plants can recover nutrients such as nitrogen and phosphorus from contaminated waters in those agricultural practices. They can also remove or accumulate metals, radionuclides, and other pollutants in their tissues. In addition, the duckweed can be used as a feed source for livestock and poultry as well as an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 101 publications
2
14
2
1
Order By: Relevance
“…For ADF, the values obtained in the present study were slightly higher than the previously reported value of 15.6% for Lemna gibba (Landesman et al, 2010) and lower than the previously reported values of 35.8 to 41.4% for Salvinia molesta (Leterme et al, 2009). For ash, values of 23% in DM for L. laevigatum (Aponte et al 2013) and 20.1% in DM for Salvinia molesta (Leterme et al, 2009) have been reported; our results were slightly lower than those reported by other authors.…”
Section: Chemical Compositioncontrasting
confidence: 96%
“…For ADF, the values obtained in the present study were slightly higher than the previously reported value of 15.6% for Lemna gibba (Landesman et al, 2010) and lower than the previously reported values of 35.8 to 41.4% for Salvinia molesta (Leterme et al, 2009). For ash, values of 23% in DM for L. laevigatum (Aponte et al 2013) and 20.1% in DM for Salvinia molesta (Leterme et al, 2009) have been reported; our results were slightly lower than those reported by other authors.…”
Section: Chemical Compositioncontrasting
confidence: 96%
“…As a result, the cove-water can be classified as eutrophic ( Carlson, 1977 ). The presence of dense mats of three duckweed species ( Baker, 2018 ) also indicates that the water is eutrophic ( Landesman et al, 2011 ). The likely source of nutrients is the Clinton River Bypass ( Figure 1 ), a waterway high in nutrient and sediment pollution ( Healy et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Duckweed species have been used for over 30 years to recover nutrients from wastewaters [ 9 - 18 ]. They are also a good source of proteins and starch, which are essential for the production of value-added products such as animal feed and also for bio-ethanol applications [ 19 - 21 ].…”
Section: Introductionmentioning
confidence: 99%